Implementasi Teknologi Web Geospasial dan Decision Tree untuk Klasifikasi Sebaran Pengumpulan Zakat - Pratiwi Susanti; Moch Yusuf Asyhari; Juwari Juwari; Khairul Adila Ahmad; Norin Rahayu Shamsuddin; Taniza Tajuddin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
As one of the five pillars of Islam, zakat significantly contributes to socio-economic development and growth in a region. Zakat collection in the city of Madiun has various challenges, including the motivation of muzakki as zakat payers. Zakat is an obligation for someone with assets or income exceeding basic needs to fulfill their living needs. One way to increase motivation to pay zakat is using geospatial web technology to map muzakki in the city of Madiun. Muzakki report data, which previously had the form of a graphic diagram, was changed to a more interactive geospatial form. Several essential advantages in its implementation include embedding precise coordinate points to facilitate the geospatial-based monitoring process, important notes and information about muzakki, and the classification of zakat collection, including collecting zakat in high, medium, and low amounts. This method can represent muzakki mapping more easily and clearly so that zakat institutions (BAZNAS) can quickly determine their policies to increase zakat collection.